Proceedings of the 2018 Asian American/Pacific Islander Nurses Association Conference: Local to Global--Future Directions for Research on Health Disparities - Jillian Inouye (JMIR Publications, 2018)
The Asian American / Pacific Islander Nurses Association's 15th Annual International Conference was held September 22-23, 2018 at the Hilton Garden Inn, located in Southpoint, Durham, S.C. with 43 research presenters. The conference theme was Local to Global: Future Directions for Research on Health Disparities with a dozen internationally well-known leaders around the world as keynote and special session speakers. Drs. Hyeoneui Kim, PhD, MPH, RN; Duke University School of Nursing and Jeeyae Choi, PhD, RN; University of North Carolina Wilmington School of Nursing were co-chairs and led the conference topics which addressed the current trends and future directions of health disparity research among AAPIs. The abstracts published here represent concurrent sessions focusing on the topics of: Nurses as Leaders- from Bedside to Board Room Moderator; Emerging Evidence and Future Directions of Clinical Practice; Paradigm Shift in Nursing Education to Influence Patient and Staff Safety and Patient Care Outcomes; Culturally Tailored Chronic Disease Care to Improve Patient Satisfaction and Patient Care Outcomes; The Use of Technology in Nursing Research; and Leveraging Technology for Practice, Research, Education. As the only journal focusing on (API) health and nursing we hope these topics give a flavor of areas important to API.